IMPLEMENTASI KEBIJAKAN RUANG LAKTASI DALAM MENDUKUNG PEMBERIAN ASI EKSKLUSIF BAGI IBU PEKERJA - Rahayu Mujiharti (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
ABSTRACT One factor that results in the low exclusive breastfeeding is the status of the working mother. The function of exclusive breastfeeding can prevent babies from developing diseases, help the baby's brain and physical development and can reduce infant mortality. The impact of babies who are not exclusively breastfed is an increase in medical costs, In supporting the program of exclusive breastfeeding in the workplace, the government has made policies in the form of laws, government regulations and joint regulations of 3 ministers regarding increasing exclusive breastfeeding during working hours at work and PERMENKES No.15 of 2013 regarding the provision of lactation space many workplaces have not implemented these policies. The policy of providing lactation space is a demand for workplaces both in government agencies and private companies to implement this policy and make the workplace friendly in terms of breast feeding. The main objective of this research is to conduct a literature study on the implementation of policies on providing lactation space in support of exclusive breastfeeding for workers. This research method uses a literature review. This study includes literature published from 2006 to 2019 and listed on DOAJ, Garuda, and PubMed-NCBI. The results of the implementation of the breast feeding room policy in supporting the provision of exclusive breast milk (ASI) for workers show that there are differences where, there are policies that have implemented policies but have not been optimal.